EFFICIENCY OF THE ACTIVITIES OF BANKING INSTITUTIONS IN UKRAINE - CHAIKOVSKYI, Yaroslav; CHAIKOVSKA, Ivanna; CHAIKOVSKYI, Yevhen (Scientific journal «World of Finance», 2023)
Introduction. The article examines statistical data on the number of banks that have a banking license, banks with foreign capital and the dynamics of the influence of foreign capital on the Ukrainian banking system in 2010–2021. The analysis of the dynamics of bank assets and liabilities and the share of bank assets in the gross domestic product is carried out of Ukraine in 2010–2021. The structure of ownership of the assets of the banking system, the dynamics of income, expenses, financial results, return on assets (ROA) and return on capital (ROE) of banks of Ukraine were studied. The conclusions regarding the current state and efficiency of operations were substantiated banks in 2010–2021.The purpose of the article is to analyze the efficiency of banking institutions in Ukraine in 2010–2021, to assess the capital concentration of the Ukrainian banking system and to substantiate the directions for increasing the efficiency of the functioning of the Ukrainian banking sector in modern conditions.Methods. Statistical methods, methods of techno-economic and financial analysis and observation are used to study development trends, the current state of functioning of the banking system of Ukraine. Statistical and graphic methods are used for processing and generalization of statistical data and their display in tables and figures. On the basis of the dialectical method of cognition, the ownership structure of the banking system, the dynamics of income, expenses, financial results, return on assets (ROA) and return on capital (ROE) of Ukrainian banks are summarized. The system method was used when studying the level of concentration of the banking system.Results. The study of trends in the development of the main indicators of banks' activity in Ukraine shows that during the analyzed period the number of commercial banks systematically decreased. At the same time, during the same period, the value of assets and liabilities of the banking sector increased. Banks occupy the leading place in the financial services market of Ukraine. However, for the modern banking system, there is a noticeable tendency towards a gradual decrease in the share of bank assets in GDP. In the analyzed period, the ownership structure of the banking system underwent significant regrouping in the groups of banks with a state share, banks of foreign banking groups, and banks with private capital. As a result of the transfer in 2016 of the system JSC CB “Pryvatbank” to 100% ownership of the state, the share of state banks in the structure of assets of the banking system has increased significantly. The banking market of Ukraine is concentrated, as evidenced by the values of the share of the largest bank in net assets (CR1), the five largest banks in net assets (CR5), the ten largest banks in net assets (CR10), the largest twenty banks in net assets ( CR20) and the Herfindahl-Hirschman index (HHI). The volume of non-performing loans (NPL) in Ukrainian banks was considered.Conclusions. Today, the banking sector has successfully adapted to work in the conditions of a pandemic and martial law and is properly performing its functions, supporting the economy. According to the results of recent years, the banking sector has been making profits. The profitability of assets and capital of the banking sector is growing. Increasing the efficiency of Ukrainian banks through cost reduction, the search for new sources of income, mainly commissions, through expanding the areas of interaction between banks and clients, in particular remote banking services, the use of modern innovations, financial technologies requires further scientific research.